Myricetin ameliorates cerebral ischemia/reperfusion damage in rat four vessel occlusion model: Histological, biochemical, molecular findings (Annals of Medical Research, 2023)
Aim: Due to the loss of neurons and neural network functions in the brain, cerebral ischemia is the leading cause of permanent disability in adults all over the world. Antioxidants scavenge free radicals and protect tissues against oxidative damage caused by ischemia/reperfusion. This study aims to investigate the protective effects of myricetin, a powerful antioxidant, against cerebral ischemia/reperfusion injury.Materials and Methods: There were 5 experimental groups in this study; control, sham, ischemia/reperfusion (I/R), Myricetin 3 (Myr 3), and Myricetin 6 (Myr 6), and 8 rats in each group. Four-vessel occlusion was made to create ischemia. The ischemia and subsequent reperfusion period were 30 minutes each. One hour before ischemia, 3 mg/kg of myricetin was given to rats in the Myr 3 group and 6 mg/kg of myricetin was given to rats in the Myr 6 group. GolgiCox and Caspase3 stainings were carried, SOD, and MDA levels were investigated, and TNF-α mRNA expression levels were measured in brain tissue.Results: This study’s results showed that; the number of neurons decreased drastically in the CA1region of the hippocampus in the I/R group. Distance between cells increased, and the neurons were spaced apart and randomly distributed. Neuronal loss in the hippocampus was reduced and the amounts of neurons rise in the Myr 3 group compared to the I/R group. A significant decrease was detected in the SOD values of the I/R group.  Compared to the I/R group, the SOD values of Myr 3 and Myr 6 groups increased significantly. MDA level of the I/R group increased significantly compared to the control. MDA values of Myr 3 and Myr 6 groups decreased significantly when compared to the I/R group. TNF-α mRNA expression level was significantly higher in the I/R group. A significant reduction was observed in the mRNA expression level in the Myr 3 group.Conclusion: In conclusion, the findings of this study suggest that myricetin is a promising agent for inhibiting the ischemia-induced cerebral inflammatory response and oxidative stress.